The value for money factors and their interrelationships for smart city public–private partnerships projects - Almarri, Khalid (2022)
Purpose The amount of expenditure required to scale up smart infrastructure projects is often enormous. Public–private partnership (PPP) is one of the proposed and viable solutions for addressing the financial issues of smart infrastructure projects. However, the most important criterion in choosing PPP over other procurement methods is that the project under the PPP method should deliver the best value for money (VFM) while also including defined economic and social objectives, rather than relying exclusively on efficiency factors. While PPP provides a variety of advantages for developing infrastructure, significant challenges may arise as a result of smart infrastructure initiatives. Diverse PPP approaches have been used to build smart infrastructure around the world, with varying degrees of success. The purpose of this study is to identify the VFM factors that are suitable for smart infrastructure projects and to examine the impact of their interrelationships. Design/methodology/approach The methodology for this study consisted of three stages: identifying VFM factors in PPP for smart cities based on an extensive literature review, analyzing data from a sample of 90 PPP practitioners using a Likert scale questionnaire and estimating interrelationships among VFM factors using structural equation modeling (SEM). Findings After performing a SEM analysis on the gathered data, the best fitted measurement model consisted of 11 VFM factors acting as indicators of three latent variables for smart infrastructure projects (clear output specification for measuring performance, efficient dispute resolutions, optimized risk allocation and business models, improved and integrated community services, economic sustainability, appropriate capital structure and collaterals, smart asset management, diffusion of smart technologies, technical innovation, Ince) and three clusters of their interrelations (economic sustainability, integration drive, optimization and smart technology). Practical implications This research has resulted in a useful and readily applicable list of factors and clusters of value for money criteria for the implementation of PPP in smart infrastructure projects, assisting public sector management by providing a measure of pre-conditions that can be used as an assessment tool when determining whether a PPP should be used instead of conventional methods. Originality/value In addition to the theoretical and methodological contributions, this study produced a usable and readily adaptable list and clusters of value for money factors for the implementation of PPP in smart infrastructure projects.